Determinants of Poverty in Central Java Province in 2018-2022 - Al-Khalil, Ikpram Azizi; Rochmatullah, Mahameru Rosy (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to investigate the relationship between economic and social indicators and poverty rates. The research focuses on four key indicators: GRDP, PAD, HDI, and TPT. The method was a quantitative research approach. Findings reveal a significant relationship between indicators and poverty rate; economic growth (GRDP, PAD) leads to job creation and poverty reduction; improved HDI (education, health, standard of living) alleviates poverty; lower TPT indicates less poverty. The authors emphasize the need for an integrated development strategy that considers both economic growth and social well-being. Collaboration between government agencies is crucial for effective policy implementation and poverty reduction.